The Relationship Between Hemoglobin Levels and Early Mobilization on Surgical Wound Healing in Post Sectio Caesarea Patients at Metta Medika Padangsidimpuan Hospital - Milani, Dianra; Fransisca Wijaya, Johanna; Aisyah Dalimunthe, Siti (Syntax Corporation Indonesia, 2025)
This study aims to analyze the relationship between hemoglobin (Hb) levels and early mobilization on surgical wound healing in post-sectio caesarean section patients. The research design uses a quantitative approach with a cross-sectional analytical observational method. The study was conducted at Metta Medika Padangsidimpuan Hospital on 33 patients who were selected using the purposive sampling technique. The data was analyzed by the Chi-Square test to determine the relationship between variables. The results showed that the Hb level ≥ 11 g/dl was related to better healing of surgical wounds compared to Hb < 11 g/dl (p = 0.013). In addition, rapid and normal early mobilization significantly improved wound healing compared to slow mobilization (p = 0.025). This study concluded that Hb levels and early mobilization had a significant relationship with wound healing in post-sectio caesarean section. These findings can be used as a reference in postoperative management to improve the quality of patient recovery.